GRP-119 Most Frequent Drug-Related Events Detected by Pharmaceutical Analysis of Computerized Physician Order Entry and Proposed Solutions. (12th March 2013) - Chu, N; Gorce, T; Duhalde, V; Cestac, P; Vie, M; Bellon, B
Abstract : Background: In 2012, Toulouse University hospital implemented a Computerized Physician Order Entry (CPOE) system in two digestive surgery departments (41 inpatient beds). Clinical pharmacists in the wards contribute to safeguarding the medication process by reviewing prescriptions. Purpose: To highlight recurrent and avoidable drug-related problems identified by pharmaceutical analysis of CPOE and to raise physicians' awareness regarding these prescription problems. Materials and Methods: From April to July 2012, Pharmaceutical Interventions (PIs) concerning prescription problems were recorded in the CPOE according to the codification defined by the working group of the French Society of Clinical Pharmacy. We extracted the following data from the CPOE: drugs, type of problems and PIs. We identified the main prescription problems and drugs involved. After data analysis, preventive measures were submitted to the physicians. Results: 2396 prescriptions were analysed and 450 Pharmaceutical Interventions (PIs) were accepted by physicians (18.8%). Main prescription problems concerned analgesics (52 PIs made): inappropriate administration and dosage errors; heparins (31 PIs): dosage errors; antiemetics (24 PIs): dosage errors and drug-drug interactions; antibiotics (16 PI): inappropriate prescription. To prevent these problems, a multi-disciplinary group was set up with physicians, nurses and pharmacists. This group has reviewed standardised order sets and has developed a pocket guide to help new residents while prescribing. Conclusions: This study describes the most frequent CPOE problems. Communication and collaboration with physicians and nurses are the key to reducing avoidable adverse drug events and to safeguarding CPOE. No conflict of interest.